Rural development : principles, policies and management - Singh, Katar; Shishodia, Anil (New Delhi : SAGE Publications India Private Limited, 2016)
An unparalleled textbook on the subject, extensively revised to provide updates of various policies, strategies, and programs in the spheres of rural development and management in India.
Keywords: Rural development; Rural development -- India -- Case studies